Egg development of Trematomus eulepidotus Regan, 1914 (Nototheniidae, Pisces) from the Weddell Sea, Antarctica ... - Ekau, Wemer (Cybium, 1989)
During the third cruise of the German RV Polarstern to the Weddell Sea in Jan./Feb. 1985, a sample of approximatively 2,000 fertilized eggs of Trematomus eulepidotus was collected with a bottom trawl. About half of these eggs were transferred to an aquarium and incubated over a period of 5 months. The development of the egg took 131 to 159 days from stage I (gastrulation stage) to hatching at a mean temperature of about 0°C. Larval length at hatching was 18.6 mm standard length. ...